智慧創作專用權之性質與使用倫理─給原創條例的幾點建議 The Legal Character and Culturally Appropriate Practices of Traditional Indigenous Intellectual Creations—Suggestions for the Protection Act for the Traditional Intellectual Creations of Indigenous Peoples - 林孟玲 Meng-Ling Lin (Kējì Fǎxué Pínglùn, 2015)
原住民族智慧創作保護條例的制定，對於保護原住民族的傳統智慧創作、文化成果之表達有顯著的貢獻。原創條例雖然立法意旨甚佳，是專門為保護原住民族傳統智慧創作所量身定作之立法，也注意到了原住民族智慧創作有別於著作權之概念，而做出調整。但是條例所用的權利保護概念，卻仍沿用著作權之規定，是美中不足之處。例如：「智慧創作專用權」的內涵仍沿用著作權的權利概念「智慧創作財產權」與「智慧創作人格權」；如果對於智慧創作專用權造成侵害，智慧創作專用權人的救濟管道與著作權受侵害的救濟方式並無二致，包括：排除侵害請求權、請求防止侵害請求權、損害賠償請求權、請求銷毀侵害智慧創作之物。此外，原創條例並未提及使用原住民族之傳統智慧創作時，不能違反原住民族傳統價值等觀念，有如進行關於原住民族的學術研究時，有特別應遵守的研究倫理。本文從智慧創作專用權性質之討論出發，繼而探討智慧創作財產權與智慧創作人格權之內涵。舉例說明基於部落習慣法而來的，智慧創作之使用所應注意之使用倫理後，最後亦根據部落習慣法，闡述現行智慧創作專用權之權利救濟管道妥適性。本文之建議期使原創條例能真正落實其立法目的：保護原住民族傳統智慧創作以及促進原住民族文化發展。 The enactment of the Protection Act for the Traditional Intellectual Creations of Indigenous Peoples makes great contributions to the development and protection of indigenous traditional intellectual creations by adopting indigenous legal concepts suitable to tribal culture. For example, it recognizes collective rights to indigenous creations. Also, it recognizes that the period for legal protection of indigenous traditional intellectual creations as an exclusive right is permanent. However, concepts of traditional intellectual creation, economic right, moral right, and remedies in this act still derive from Copyright Law, and remain inadequate for proper adoption of indigenous tribal common law. Also, the Act does not refer to nor adopt culturally appropriate practices of traditional intellectual creations, which is very important to indigenous peoples in order to prevent cultural appropriation, but also to foster respect between cultures. This article thus gives some examples to elaborate these significant concepts, including indigenous traditional intellectual creation exclusive rights, traditional intellectual creation economic right and moral rights, culturally appropriate practices regarding indigenous traditional intellectual creations, and culturally appropriate remedies when traditional intellectual creation exclusive rights are infringed. These suggestions should help to better protect and promote indigenous traditional intellectual creations and cultures in appropriate fashion.